Effect of soil physical properties on soil infiltration rates - Fera @ Nony Cleophas; F. Isidore; Baba Musta; B.N. Mohd Ali; Maznah Mahali; Nur Zaida Zahari; Kawi Bidin (Faculty of Science and Natural Resources, 2021)
The physical properties of the soil are studied to understand the influence of soil properties on infiltration rate. The results of simple regression analyses showed that there was little association of the physical properties of the soil and the infiltration rate. This study suggests that high variation of infiltration rate in this study site is attributed to the high spatial variability of soil properties.